2019
DOI: 10.1096/fj.201802291r
|View full text |Cite
|
Sign up to set email alerts
|

A variant in a microRNA binding site in NEIL2 3′UTR confers susceptibility to age‐related cataracts

Abstract: DNA damage in lens cells is considered a critical trigger for the onset of age‐related cataracts (ARCs). Among DNA repair pathways, the base excision repair (BER) pathway is responsible for mending single‐strand breaks in DNA. In this case‐control study with 993 ARC cases and 993 healthy controls, we genotyped 9 single‐nucleotide polymorphisms (SNPs) within microRNA (miRNA) regions of 6 BER pathway genes and examined their associations with ARC susceptibility. We identified rs4639:T > C in the Nei‐like DNA gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In our study, we found that NEIL2 G/G genotype for rs4639 was associated with 0, 49-fold decreased risk of BCa. This inverse association could be explained by the fact that the minor allele interacts with some speci c miRNA, which activates the BER pathway [41]. Moreover, we have found that rs4639 and rs804276 in NEIL2 gene were in linkage disequilibrium (p-value = 0.03).…”
Section: Dna Repair Pathwaymentioning
confidence: 75%
“…In our study, we found that NEIL2 G/G genotype for rs4639 was associated with 0, 49-fold decreased risk of BCa. This inverse association could be explained by the fact that the minor allele interacts with some speci c miRNA, which activates the BER pathway [41]. Moreover, we have found that rs4639 and rs804276 in NEIL2 gene were in linkage disequilibrium (p-value = 0.03).…”
Section: Dna Repair Pathwaymentioning
confidence: 75%
“…In addition to affecting PARP-1, miRNAs may also interfere with DNA SSBs in other way. Kang et al (2019) found that miR-3912-5p might bind to 3′-UTR of BER protein NEIL2, thereby affecting DNA damage in lens cells. And miR-590 slowed the proliferation and promoted the repair of SSBs in embryonic stem cells ( Liu et al, 2014 ), but the mechanism of which is still unclear.…”
Section: Mirnas Regulate Ddrmentioning
confidence: 99%
“…The reported associations of polymorphisms in the non-coding parts of hNEIL2 include the following: risk of squamous cell oral and oropharynx carcinoma [22], testicular germ cell tumors [23], gastric cancer [24], cervical squamous cell carcinomas and intraepithelial neoplasias [25] and breast cancer [26], decreased progression-free survival in colorectal cancer patients [27], non-small cell lung cancer patients treated with cisplatin [28] and breast cancer [26], and recurrence in BCGtreated bladder cancer [29]. Also, non-coding hNEIL2 polymorphisms showed associations with addiction and behavioral disinhibition [30], susceptibility to age-related cataracts [31], and increased chromosome aberrations induced by tobacco nitrosamines [32]. Neil2 −/− mice are viable but show an increased production of pro-inflammatory cytokines upon bacterial infection or challenge with lipopolysaccharide [33][34][35].…”
Section: Introductionmentioning
confidence: 99%